PENGUJIAN THE DAY OF THE WEEK EFFECT, WEEK FOUR EFFECT, DAN ROGALSKY EFFECT TERHADAP RETURN SAHAM LQ-45 DI BURSA EFEK INDONESIA - aji, Lutfi; Djazuli, Atim (Jurnal Ilmiah Mahasiswa FEB, 2013)
Market anomaly can be describe as a technique or strategy that appear to contradict efficient market. Some reaserch about this phenomena in Indonesia Stock Exchange have defferent result. The purpose of this research is to examine the appereance daily market anomaly that are the day of the week effect, week four effect, and rogalsky effect toward stock return in Indonesia Stock Exchange January-desember 2012 period Sampel of this research is selected by using purposive sampling technique. This research samples are 35 active stocks wich is listing in LQ-45 index in Indonesia Stock Exchange. Type of data which is used is secondary data that are open and closing daily stock price during Januari-Desember 2012. The statistic methods which are used to test hypotheses are Kruskall-Wallis test, Wilcoxon right side test, and Wilcoxon left side test. The result show that the day of the week effect and week four effect exist in Indonesia Stock Exchange, but rogalsky effect doesn’t exist in Indonesia Stock Exchange during Januari-Desember 2012. Key words: stock return, the day of the week effect, week-four effect, rogalsky effect.